2019
DOI: 10.1590/1984-0462/;2019;37;3;00008
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cells Profile in Umbilical Cord of Late Preterm and Term Newborns

Abstract: Objective: To describe the hematological profile in cord blood of late preterm and term newborns and compare blood indices according to sex, weight for gestational age and type of delivery.Methods: Cross-sectional study with late preterm and term newborns in a second-level maternity. Multiple gestation, chorioamnionitis, maternal or fetal hemorrhage, suspected congenital infection, 5-minute Apgar <6, congenital malformations, and Rh hemolytic disease were excluded. Percentiles 3, 5,10, 25, 50, 75, 90, 95 and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
2
8
0
4
Order By: Relevance
“…In our study, there was no correlation between PLT and gestational age or birth weight. On the other hand, Rolim et al [16] evaluated hematologic profile in 2662 newborns including 193 late preterm, and showed that platelets remained nearly constant during gestation. These variations can be explained by differences in patient characteristics and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was no correlation between PLT and gestational age or birth weight. On the other hand, Rolim et al [16] evaluated hematologic profile in 2662 newborns including 193 late preterm, and showed that platelets remained nearly constant during gestation. These variations can be explained by differences in patient characteristics and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The differentials of preterm CB samples differed significantly from those of normal term samples, with lower neutrophils, high lymphocytes, and lower basophils percentages. In a previous study, CBC performed on preterm CB samples indicated low neutrophil counts in preterm compared to term CB samples, with no difference in lymphocyte counts between preterm and term CB samples [17].…”
Section: Discussionmentioning
confidence: 99%
“…Just a few studies investigated gender differences in neonatal coagulation. An early study reported that female neonates had a more active thrombocytopoiesis and higher PLT than males in neonatal cord blood [29,30] ,and the gender signi cance in PLT values would be indicated after two years old [31].…”
Section: Discussionmentioning
confidence: 99%